Cooperative learning methods and algebraic proficiency: insights from secondary school education / Norhanis Che Aziz, Ainon Zarina Mohamed Nadzri and Zarith Sofiah Othman - Che Aziz, Norhanis; Mohamed Nadzri, Ainon Zarina; Othman, Zarith Sofiah (Universiti Teknologi MARA, Perlis, 2024)
Cooperative learning, a collaborative approach where students work together in small groups to comprehend academic content, has gained recognition as an effective pedagogical method. Algebra, a mathematical discipline employing letters and symbols to represent quantities and figures, often poses challenges for secondary school students. Despite advancements in teaching strategies, Mathematics achievement among students remains a concern. Existing literature suggests that cooperative learning may offer superior results in enhancing students' mathematical performance compared to traditional methods. This study aims to assess the influence of cooperative learning on students' proficiency in comprehending algebraic expressions. Employing a quantitative approach, data was gathered through a questionnaire. 68 samples of secondary students in Kelantan, Malaysia were obtained and analysed using SPSS. The results demonstrate a positive impact of cooperative learning on the secondary students’ achievement in understanding algebraic expressions.